Correlates of Public Relations Practitioners' Role Types in Malaysia - Ling, Liong Ing (1993)
The objectives of this study were (1) to determine the role types that could be used to describe the PRPs' roles in their organisations in Malaysia and (2) to determine the relationships between selected personal factors, organisational factor sand psychological factors with the role types that had been identified. A total of 208 names were randomly drawn from IPRM's membership. Data was gathered employing the mail questionnaire method.Seven hypotheses were formulated to be tested using attest for correlated samples of which the correlation coefficients of the selected in dependent variables were transformed into standard correlations or the Fisher's Z scores. The study revealed that the two role types as suggested by several researchers could also be used to describe the types of roles the PRP sin Malaysia performed.